Improving Learning Outcomes of Class IV.B Students by Using Learning Videos at SD Negeri 04 Sontang - Nisful Laili (BiCED Proceeding, 2024)
This study aims to improve students' learning outcomes in the material Learning to Read and Interpret QS. At-Tin through the implementation of video-based learning. This classroom action research was conducted in two cycles involving 20 students. Data were collected through learning outcome tests, observation sheets, and interviews. The findings reveal an improvement in students' learning outcomes. In the first cycle, the students' average score reached 84.75, with a mastery level of 76.17%, while in the second cycle, the average score increased to 94.44, with a mastery level of 86.67%. The use of video-based learning also enhanced student engagement, from 60% in the first cycle to 80% in the second cycle. However, challenges such as students' adaptation to the new method and teachers' management of learning processes were identified. This study concludes that video-based learning is an effective alternative to improve students' learning outcomes.